Gender Representation on Visual Illustrations in Indonesia EFL Textbook - Devianti Liannita; Aridah Aridah; Ruel T. Bonganciso (Journal of English as A Foreign Language Teaching and Research, 2023)
The urge of gender equality had been going on for several decades and even though people were aware of it yet there was no significant result toward the effort. Not to neglect all the intended purposes of many studies previously, still somehow the significant differences were less shown in the practice. In order to identify such matter, hence the study was conducted. The visual illustrations in textbook were not only as the aesthetic aspect of one but also to represent matters that could easily be understood better by visualization. The gender representation was analyzed by its numbers of appearances, ratio and also the settings of each gender was situated in the illustrations. By the end of the study, it could be stated that the lack of female representation in appearance and ratio issue was still existing in the textbook. However, in most of the illustrations, both of the genders were situated in social settings in general though there were several in domestic ones. The further study was needed in order to analyze the other elements of the textbook.